Optimal Coordination of DOCR for Radial Distribution Systems in Presence of TCSC - Lazhar Bougouffa; Abdelaziz Chaghi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
Protective relays coordination is the process of determining the exact relay settings such that the relay closes to the fault would operates faster than other relays. The operating time of each relay depends on two independent variables called Pickup current (Ip) and Time Dial Setting (TDS). In this paper, a PSO algorithm has been presented to determine the coordination of Directional Over-Current Relays (DOCRs) in presence of multi-system FACTS devises. From the simulation result and analysis, the impact of TCSC location in the in 33-bus distribution system on Directional Over-Current Relays has been observed on the optimal relays settings as well as the effectiveness of the proposed algorithm in finding optimal coordination of directional over-current relays.